2000
DOI: 10.1093/alcalc/35.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Glucuronide in Human Hair

Abstract: Ethyl glucuronide (EtG) is considered to be a promising candidate marker of alcohol consumption, but exhibits a short window of detection in blood or urine. Keratinized tissues are known to retain foreign substances and to provide a greater retrospective window of detection than body fluids. Therefore, post-mortem hair, skin swabs, and stratum corneum samples were collected from four subjects with a reported history of alcohol misuse and from seven subjects with a report of regular, socially accepted drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 7 publications
1
57
0
5
Order By: Relevance
“…In analyzing more than 1000 urine samples from clinical and forensic cases, we have found that LC-MS/MS has advantages over GC-MS analysis [16,31,32] because of higher sample throughput by shorter analysis time (10 min per run instead of approximately 20 min), no need for derivatization as in GC-MS, and less contamination of the chromatographic system.…”
Section: Discussionmentioning
confidence: 99%
“…In analyzing more than 1000 urine samples from clinical and forensic cases, we have found that LC-MS/MS has advantages over GC-MS analysis [16,31,32] because of higher sample throughput by shorter analysis time (10 min per run instead of approximately 20 min), no need for derivatization as in GC-MS, and less contamination of the chromatographic system.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and fear of delay or exclusion from the transplant process may lead patients to deny use or attempt to falsify toxicology screens (1) (17). In the addictions field, the goal of a long-term marker for alcohol consumption has been realized through analysis of EtG in hair, with heavy drinkers differentiated from nondrinkers and light drinkers (18,19 (23) …”
Section: Introductionmentioning
confidence: 99%
“…EtG is minor metobolite of alcohol metabolism produced when alcohol is glucoronidated with activated glucoronic acid (UDP-GA) [64]. Several studies have investigated the measurement of EtG in hair [33,[65][66][67][68][69][70][71][72][73][74][75][76]. Hair analysis of EtG has been shown to be highly specific (100%) in the detection of heavy alcohol users, however there have been variable reports with regards to the test's sensitivity, ranging between 50 and 100%.…”
Section: Combined Use Of Hair Faee With Hair Ethyl Glucuronidementioning
confidence: 99%
“…Hair analysis of EtG has been shown to be highly specific (100%) in the detection of heavy alcohol users, however there have been variable reports with regards to the test's sensitivity, ranging between 50 and 100%. This variation is likely due to the large range of analytical limits of detection (LOD) reported between laboratorie [64][65][66][67][68] hermore, a previous study showed that in a cohort of heavy drinkers both FAEE and EtG hair tests were able to identify all alcoholic patients, therefore, the tests acted redundantly [68]. Consequently, it remains possible that the use of both tests may have added value for the detection of pregnant alcohol abusers; however, more research is required to determine the cost versus the benefits.…”
Section: Combined Use Of Hair Faee With Hair Ethyl Glucuronidementioning
confidence: 99%